Avaliação histológica,histoquímica e imuno-histoquímica de mastocitomas cutâneos em cães - Santos, Alex dos (2018)
Mast cell tumors (MCTs) is the most prevalent cutaneous mesenchymal tumor of the dog. In the region of Santa Maria, RS, this neoplasm corresponds to 20% of the malignant skin tumors diagnosed in the laboratory routine. The clinical-pathological diagnosis can be made through cytology, histopathological examination and immunohistochemistry. The immunohistochemical technique is used to differentiate biologically more aggressive tumors from less aggressive tumors. However, some of the currently available immunomarkers are influenced by formalin fixation, interfering with the results. The main objective of this study was to evaluate the interference of formaldehyde in the immunostaining of KIT protein and Ki67 protein in four pre-established fixation times (24, 48, 72 and 96h) in MCTs. Two amplification systems were also used to determine possible differences in detection for each one of the antibodies studied. This study was divided into two parts: a retrospective study, analyzing tissue samples from 25 cases of biopsies without knowledge of fixation time; and a prospective study, analyzing tissue samples from 12 cases with known fixation times. In both studies, two histological grading systems (Patnaik and Kiupel), the special staining of toluidine blue and the immunohistochemistry for KIT and Ki67 proteins were applied. Additionally, in the prospective study, two amplification systems (biotinylated and not biotinylated) for the Ki67 protein and the AgNOR technique (counting of the argirophilic nucleolar organizing regions) were tested. It was observed that the fixation for up to 96h did not interfere in the immunohistochemical evaluation for the KIT protein. However, for Ki67 protein, there was marked interference when the fixation was greater than 24h. Both amplification systems showed satisfactory results. However, there were no differences and/or improvement in the results of immunostaing for Ki67 when compared the amplification systems. The additional useof the AgNOR method to evaluate the rate of cell proliferation is suggested when the fixation time of the neoplasm is unknown or greater than 24 hours.